Semiosis Process and Meaning-Making on Bron’s Menu - Agus Darma Yoga Pratama (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
This research aimed to know the semiosis process and meaning-making about how words and pictures on the menu can contribute to better business and achieving customer satisfaction by applying the theories from Pierce (1996) and Ogilvy (1985). Data were taken from BRON – The Urban café's menu, especially in snack and oriental categories. The data were collected by reading the menu list, observing the picture of the menu list, and checking the appropriateness between pictures and words. The collected data were then analyzed using Pierce and Ogilvy's theories. The analysis showed that representamen, object, and interpretant are interrelated in the semiosis process to present the uniqueness and authenticity of BRON – The Urban Café’s menus such as garlic cassava, vegetarian spring rolls, crispy banana spring rolls, French fries, and nasi goreng nusantara. The meaning-making with words and pictures in the list menus is mostly accurate and implicit, but it is still known and acceptable due to the customer’s familiarity with the cooking techniques, ingredients, and serving of the food also the effect of brand image, the relevance of preexisting knowledge, big idea, and others.